2014
DOI: 10.1093/aepp/ppu009
|View full text |Cite
|
Sign up to set email alerts
|

Food Insufficiency and Income Volatility in US Households: The Effects of Imputed Income in the Survey of Income and Program Participation

Abstract: This paper explores how the use of imputed earnings data to measure income in the Survey of Income and Program Participation affects the observed relationship between household income volatility and food insufficiency. The study finds that the inclusion of imputed earnings data when measuring income volatility substantially understates the association between large drops in household income and food insufficiency. After excluding observations with imputed earnings, large drops in income are associated with a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
(21 reference statements)
1
12
0
Order By: Relevance
“…In particular, household economic resources are far from the entire story; 57.9% of households with an income below the poverty level were food secure in 2013, while 6.7% of households with an income exceeding 185 percent of the poverty line were food insecure (Coleman-Jensen et al 2014). The established, positive relationship between income and food security is as expected (Gundersen and Gruber 2001; Leete and Bania 2010; Dahl et al 2014). However, the substantial fraction of poor households that are food secure and the large portion of non-poor households that are food insecure is counterintuitive and in need of explanation.…”
Section: Introductionsupporting
confidence: 76%
“…In particular, household economic resources are far from the entire story; 57.9% of households with an income below the poverty level were food secure in 2013, while 6.7% of households with an income exceeding 185 percent of the poverty line were food insecure (Coleman-Jensen et al 2014). The established, positive relationship between income and food security is as expected (Gundersen and Gruber 2001; Leete and Bania 2010; Dahl et al 2014). However, the substantial fraction of poor households that are food secure and the large portion of non-poor households that are food insecure is counterintuitive and in need of explanation.…”
Section: Introductionsupporting
confidence: 76%
“…Monthly income at each of the eight waves was averaged and the natural log calculated. We followed prior research by using pretax income (e.g., Dahl, DeLeire, & Mok, ; Leete & Bania, ). It is noteworthy that with this measure there is the possibility of understating or overstating actual income fluctuations for certain households (e.g., underestimates can occur if tax rebates translate into short‐term variability in disposable income while overestimates can occur if such rebates are used to smooth consumption).…”
Section: Methodsmentioning
confidence: 99%
“…The SIPP used hot deck imputation to address missing income values (Westat, 2007), which may have systematically affected estimates of income instability (Dahl et al, ). This method replaced any missing value with the value from a randomly selected case that was observationally similar on a number of variables.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, the possibility of the phenomenon among households with incomes below 200 percent of the poverty level ranged from 4.4 percent to 5.3 percent. Similarly, Dahl et al (2014) revealed that families that experienced significant income drops had a 31 percent chance of experiencing food insecurity in the United States. Mabiso et al (2014) asserted that volatility in food prices could engender erratic caloric intake of healthy foods, especially in rural Mozambique households whose primary source of income comes from non-farm employment.…”
Section: Literature Reviewmentioning
confidence: 99%